2019
DOI: 10.1111/papt.12260
|View full text |Cite
|
Sign up to set email alerts
|

Understanding, treating, and renaming grandiose delusions: A qualitative study

Abstract: Background Grandiose delusions are arguably the most neglected psychotic experience in research. Objectives We aimed to discover from patients: whether grandiose delusions have harmful consequences; the psychological mechanisms that maintain them; and what help patients may want from clinical services. Design A qualitative interview design was used to explore patients’ experiences of grandiose delusions. Method Fifteen patients with past or present experiences of grandiose delusions who were attending psychiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 28 publications
1
50
0
Order By: Relevance
“…These findings are also interesting in light of a recent qualitative study of grandiose delusions, which identified a number of potential maintenance factors in the experience of grandiosity: meaning-making, anomalous experiences, mania, fantasy elaboration, reasoning biases, and immersive behaviors (28). We note some overlap with maintenance factors of paranoia-for instance sleep disturbances are characteristic of mania, and negative self-beliefs may motivate meaningmaking-which are in line with our findings of significant (but relatively less robust) associations between grandiosity, sleep and negative self-beliefs in the current sample; yet the cognitive-behavioral model is relatively distinct from that of paranoia.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…These findings are also interesting in light of a recent qualitative study of grandiose delusions, which identified a number of potential maintenance factors in the experience of grandiosity: meaning-making, anomalous experiences, mania, fantasy elaboration, reasoning biases, and immersive behaviors (28). We note some overlap with maintenance factors of paranoia-for instance sleep disturbances are characteristic of mania, and negative self-beliefs may motivate meaningmaking-which are in line with our findings of significant (but relatively less robust) associations between grandiosity, sleep and negative self-beliefs in the current sample; yet the cognitive-behavioral model is relatively distinct from that of paranoia.…”
Section: Discussionmentioning
confidence: 70%
“…Although seemingly counter-intuitive, the "delusion as defense" model suggests that grandiose beliefs serve to protect feelings of worthlessness and vulnerability (27). Furthermore, insomnia is commonly reported as a precursor to the development of grandiose beliefs (28). While theoretically compelling, the contribution of worry, negative self-beliefs, and sleep quality to grandiosity requires continued study (22).…”
Section: Introductionmentioning
confidence: 99%
“…This might be achieved by ordering the delivery of interventions in line with individual outcome priorities and preferences. Researchers are increasingly exploring the value of targeting treatments to specific difficulties based on patient preference [ 26 , 27 ], and future qualitative research can enhance this approach by exploring and informing treatment for specific aspects of psychosis [28] .…”
Section: Discussionmentioning
confidence: 99%
“…That delusions commonly involve a belief of having a radically altered social status (e.g., C. Green et al, 2006 ; Isham et al, 2019 ) and that, independently, social exclusion and social distance are risk factors for psychosis ( Jongsma et al, 2020 ) suggest that cognitive mechanisms involved in the perception and processing of social status may be an important site of pathology. Processes involved in perceiving and managing social status are common across a range of social species, including humans; have an evolutionarily important social function ( Chiao, 2010 ); and do not seem to be explainable solely in terms of mentalization ( Rushworth et al, 2013 ).…”
Section: Hypotheses Regarding the Role Of Coalitional Cognition In Dementioning
confidence: 99%